Investigation on Dynamic Response of Rubber in Frictional Contact - Nakano, Ken; Kawaguchi, Kai; Takeshima, Kazuho; Shiraishi, Yu; Forsbach, Fabian; Benad, Justus; Popov, Mikhail; Popov, Valentin L. (Frontiers in Mechanical Engineering, 2019)
In the present work, we analyze a device for measuring dynamic response of rubber in sliding contact. The principle of the device is to measure excited oscillations of a mechanical system with a sliding contact between a rubber roller and a rigid surface. Depending on the contact properties, varying oscillation amplitudes are measured. The goal is to determine dynamic response properties of rubber from oscillating tests. For this sake, an analytical model is introduced in which the contact problem and system dynamics are considered in detail. Analytical and numerical results obtained for this model are compared with some experimental data and discussed both on a qualitative and quantitative level.